2020
DOI: 10.2147/ott.s235037
|View full text |Cite
|
Sign up to set email alerts
|

<p>The lncRNA LINC01194/miR-486-5p Axis Facilitates Malignancy in Non-Small Cell Lung Cancer via Regulating CDK4</p>

Abstract: Background: This experimental design was based on lncRNA LINC01194 to explore the pathogenesis of NSCLC. Methods: RT-qPCR was used to detect the expression of lncRNA LINC01194 and miR-486-5p in NSCLC tissues and cell lines. CCK-8, colony formation, and transwell assays were used to examine the effects of lncRNA LINC01194 and miR-486-5p on NSCLC cell proliferation and migration invasiveness. For target gene prediction and screening, luciferase reporter assays were used to verify downstream target genes for lncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Previously, LINC01194 has been suggested to play oncogenic parts in several different cancer types, such as colorectal cancer [ 14 ] and laryngeal squamous cell carcinoma [ 21 ]. Importantly, a recent work also indicated LINC01194 as a carcinogene in NSCLC [ 22 ]. Consistent with these findings, here we discovered the upregulation of LINC01194 in LUAD tissues and cells, and that silencing LINC01194 hampered LUAD cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, LINC01194 has been suggested to play oncogenic parts in several different cancer types, such as colorectal cancer [ 14 ] and laryngeal squamous cell carcinoma [ 21 ]. Importantly, a recent work also indicated LINC01194 as a carcinogene in NSCLC [ 22 ]. Consistent with these findings, here we discovered the upregulation of LINC01194 in LUAD tissues and cells, and that silencing LINC01194 hampered LUAD cell proliferation, migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggested that downregulation of miR-486-5p contributes to the progression of NSCLC, and miR-486-5p could be a potent tumor suppressor in NSCLC [ 13 , 15 , 29 31 ]. To test whether propofol regulated drug resistance of NSCLC cells via miR-486-5p, the following function compensation assay was conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Transwell experiment was used to determine cell migration and invasion, as reported previously [ 21 ]. A chamber of 8 μm pores (6.5 mm) (Corning Costar Corp., USA) was used in the experiment.…”
Section: Methodsmentioning
confidence: 99%